An Osteoporosis Susceptibility Allele at 11p15 Regulates SOX6 Expression by Modulating TCF4 Chromatin Binding. (17th April 2022) - Zhu, Dong‐Li; Chen, Xiao‐Feng; Zhou, Xiao‐Rong; Hu, Shou‐Ye; Tuo, Xiao‐Mei; Hao, Ruo‐Han; Dong, Shan‐Shan; Jiang, Feng; Rong, Yu; Yang, Tie‐Lin; Yang, Zhi; Guo, Yan
ABSTRACT: Osteoporosis is an age‐related complex disease clinically diagnosed with bone mineral density (BMD). Although several genomewide association studies (GWASs) have discovered multiple noncoding genetic variants at 11p15 influencing osteoporosis risk, the functional mechanisms of these variants remain unknown. Through integrating bioinformatics and functional experiments, a potential functional single‐nucleotide polymorphism (SNP; rs1440702) located in an enhancer element was identified and the A allele of rs1440702 acted as an allelic specificities enhancer to increase its distal target gene SOX6 (~600 Kb upstream) expression, which plays a key role in bone formation. We also validated this long‐range regulation via conducting chromosome conformation capture (3C) assay. Furthermore, we demonstrated that SNP rs1440702 with a risk allele (rs1440702‐A) could increase the activity of the enhancer element by altering the binding affinity of the transcription factor TCF4, resulting in the upregulation expression of SOX6 gene. Collectively, our integrated analyses revealed how the noncoding genetic variants (rs1440702) affect osteoporosis predisposition via long‐range gene regulatory mechanisms and identified its target gene SOX6 for downstream biomarker and drug development. © 2022 American Society for Bone and Mineral Research (ASBMR). Abstract : Graphic representation of our model of the regulatory relationships between TCF4, rs1440702 and SOX6 for risk prediction in osteoporosis. The osteoporosis risk A allele of rs1440702 increased TCF4 binding and upregulates SOX6 expression, which may lead to increased risk of osteoporosis.